The study and optimization of the hygroscopic properties of selected natural products with an aim of designing a sanitary pad suitable for low- and middle-income population. Issue 1 (31st December 2023) - Kipchumba, Bett Brian; Kulei, Augustine Kangogo; Mwasiagi, Josphat I.
Abstract: This study came into consideration following reported cases of women and girls using unhygienic materials such as old towels to keep themselves dry during their menses. The materials can be improved in quality and usability. The polymer that replaced wood pulp is not environmentally friendly. Water hyacinth and maize stalks have proven high absorbency properties, which are from ancient and current research. The objective was to optimize the hydroscopic properties of maize stalk and water hyacinth pulp and subsequent use in the design of sanitary pad. The methodology was done according to the standard KS 507:2005. The process of extraction was done using the alkaline method, and rinsing was done to remove excess NaOH. The pulp was studied for hydroscopic properties that included the retention capacity, absorbency rate and moisture content followed by the design of the sanitary pad. The absorbency rate and the retention capacity of maize are 50% and 150 s, respectively. The absorbency properties of maize internal tissue pulp are high, and it is feasibly viable. The retention and moisture content indicate over 50% and 57%, respectively. Water hyacinth pulp has a high absorbency rate (106 s). Also, the water retention and moisture content of water hyacinth pulp is over 50% and 59%, respectively. Upon blending, the water retained and held, and absorption rate improved to 50% in 24 h, 50% (25 ml) and 2 min. The significance levels for absorbency were 15 ml to 40 ml per minute and it holds and retains up to 500 times its weight.